CONTEMPORARY IRREGULAR MIGRATIONS IN THE REPUBLIC OF SERBIA: ETHICAL NORMATIVE ASPECTS - Petrovic, Zoran (Serbian political thought, 2024)
This paper examines global and regional trends in contemporary irregular migration, which reflect complex economic, political, social, and security factors, which, as such, reflect on the Republic of Serbia. Analyzing the ethical norms of migration, the author starts from the theoretical framework of Kant's principle of general hospitality, which dictates openness to foreigners, emphasizing that in practice this principle has limitations due to real security and economic reasons. Through the ethical aspects of irregular migration, the author analyzes two categories of mandatory admission - family reunification and asylum seekers. It is shown that states have a moral obligation to enable family reunification, as well as to ensure a fair process for considering asylum applications. When it comes to discretionary admission, the author identifies permitted exclusion criteria (threat to national security, criminal history) and selection criteria (family ties, economic potential, cultural affiliation). Serbia has established a national legislative framework and is implementing best practices, continuing the trend of improving migration management policy. The paper presents current statistical indicators analyzing the current situation on the Western Balkan migration route. Migration ethics requires a complex balancing act between the sovereign rights of states, moral principles, and practical limitations, which is also reflected in the actual policies of liberal-democratic states. Through the analysis of these aspects, the paper provides insights into the ethical and normative aspects of contemporary irregular migration in the Republic of Serbia and lays the groundwork for further research and understanding of this phenomenon.
Keywords: irregular migrations; Republic of Serbia; ethical and normative aspects; migration flows